PERLINDUNGAN HUKUM TERHADAP NASABAH PINJAMAN ONLINE - Roswitha, Aji Titin; Kursiswanti, Eli Tri; Japri, Muhammad; Kristian , Agata (Collegium Studiosum Journal, 2024)
Easy credit loans online are becoming popular, but many cases have also arisen because of this. People are currently liking easy online credit loans because the process is easy and very helpful when you are in dire need and there are no funds yet. Online loans, which are usually driven by fintech companies, are also often used as loans for shopping for consumer goods in the community. Unfortunately, there are many cases of online loans that harm users. People no longer need to go to the bank to apply directly to get a loan, the process of borrowing money can simply be accessed via a smartphone, such as the Apple Store (IOS) or Google Play Store (Android) or a laptop connected to the internet. In this article the author uses a juridical approach normative, because of its approach, this model of legal research is called normative legal research. By using Primary Legal materials, the legal basis for Online Loans is regulated in Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services.